Prediction of Interest in The D3 Nautical and D3 Port and Shipping Management Study Program for New Student Admissions at State Polytechnic of Bengkalis Using Naïve Bayes - Zulyani, Zulyani; Robyansyah, Robyansyah; Rahmani, Nur; Prianus, Handro Okta (Politeknik Negeri Bengkalis, 2024)
The selection of an academic program at a higher education institution is a crucial decision that cansignificantly impact a student's academic journey. By choosing an appropriate program, students are more likely to beimmersed in an academic environment with peers, faculty, and learning conditions that align with their goals andabilities. This fosters a positive and supportive atmosphere, enables students to excel academically and acquires thenecessary knowledge to succeed in the workforce post-graduation. The Maritime Department at State Polytechnic ofBengkalis offers two study programs: D3 Nautical and D3 Port and Shipping Management. In recent years, there hasbeen a noticeable decline in the interest of prospective students in the Nautical program, while the Port and ShippingManagement program has experienced a steady increase in interest. This research employs the Naïve Bayes algorithm asa predictive model to classify student interest in the Maritime Department's programs for the 2024 new studentadmissions. The study focuses on predicting enrollment trends for the D3 Nautical and D3 Shipping Managementprograms. The results demonstrate that the Naïve Bayes algorithm is capable of predicting program interest for newstudent admissions in the Maritime Department with an accuracy of 54%, a precision of 77%, and a recall of 58%.